Spontaneous Pneumoperitoneum in a Female Patient Without Hollow Organ Perforation and Peritonitis - V. A. Golbraykh; S. S. Maskin; V. V. Matyukhin; A. G. Аrutyunyan (Неотложная медицинская помощь, 2021)
Pneumoperitoneum normally occurs due to perforation of the hollow organ of the gastrointestinal tract, which is accompanied by the development of peritonitis. Cases of free gas without perforation and peritonitis are rare. Such situations are called “nonsurgical pneumoperitoneum”. This clinical case of a patient with pneumoperitoneum and no clinical picture of acute pathology in the abdominal cavity id reported in this article. Such patients should be carefully monitored by a surgeon to avoid unnecessary laparotomy.